Pengaruh Iklan Dan Citra Merek Terhadap Keputusan Pembelian Sepeda Motor Honda Beat (Survey Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Muhammadiyah Surakarta) - Saputro, Aris Kuncoro; , Lukman Hakim, SE, M.Si (2016)
This study aims to determine the influence of advertising and brand image either partially or simultaneously to the purchasing decision Honda Beat motorcycle. This type of research is the explanation (explanatory research). The sampling technique used convinience sampling of 100 respondents. Analysis of the data used in this study is the validity, reliability, multiple linear regression, t-test, f-test, and the coefficient of determination. From the results of this study revealed that there is a positive and significant influence on purchasing decisions. Secondly there is a positive and significant influence on purchasing decisions brand image. Thirdly there is a positive and significant influence of advertising and brand image to the purchasing decision. Based on this research, Honda Beat motorcycle makers strive to create attractive advertising in various media effectively and efficiently and enhance the brand image of the impact on purchasing decisions. Because advertising and brand image influence on purchase decisions Honda Beat.